Sustainable Planning of Cross Border Cooperation Development (CBC): The factors and drivers that affect the stability of border regions - amin kooshki; mehrshad toulabi nejad (تحقیقات کاربردی علوم جغرافیایی)
In this research, the development of cross-border cooperation (CBC) to study the factors and stimuli affecting the stability of the ::::union:::: in the border regions were discussed. The aim of the present study, functional and combination method (qualitative and quantitative) is. The data-gathering tool was a questionnaire and interview. The statistical community included various experts in the fields of political science, geography, economics, sociology, law enforcement experts, governorate and governorate in Sistan and Baluchestan province. Using a targeted sampling, 70 experts were selected. For analysis of data, descriptive tests and binary logistic regression model (LM-Newton-Marcard-Raphson method) were used. The results showed that in the area of planning for unity in Sistan and Baluchestan except for the determination of the right of the Hirmand River in the Sistan region, which was concluded with the country over a period of time, the plan was not approved or implemented, and among the five factors Economic, social, cultural-religious, institutional-structural and political security, three economic factors (0.478), political-security (0.473) and cultural-religious (0.363) have the most effect on the stability of unity of border regions in Studied area. The results of this study can be used to develop border cooperation cooperation and coherence stability in different border regions of Iran.